COVID-19 measures as an opportunity to reduce the environmental footprint in orthopaedic and trauma surgery - Arndt, Eva-Maria; Jansen, Tom Rainer; Bojko, Jessica; Roos, Jonas Joachim; Babasiz, Mari; Randau, Thomas Martin; Welle, Kristian; Burger, Christof; Kabir, Koroush (Frontiers in Surgery, 2023)
Background: Climate change and its consequences on our everyday life have also tremendous impacts on public health and the health of each individual. The healthcare sector currently accounts for 4.4% of global greenhouse gas emissions. The share of the emissions in the health care system caused by the transportation sector is 7%. The study analyses the effect of video consultation on the CO2 emissions during the Covid-19 pandemic in an outpatient clinic of the department of orthopaedics and traumatology surgery at a German university hospital. Methods: The study participants were patients who obtained a video consultation in the period from June to December 2020 and voluntarily completed a questionnaire after the consultation. The type of transport, travel time and waiting time as well as patient satisfaction were recorded by questionnaire. Results: The study comprised 51 consultations. About 70% of respondents would have travelled to the clinic by car. The reduction in greenhouse gas emissions of video consultations compared to a face-to-face presentation was 97% in our model investigation. Conclusion: The video consultation can be a very important part of the reduction of greenhouse gas emissions in the health care system. It also saves time for the doctor and patient and can form an essential part of individual patient care.